Analysıs Of Students' Problem-Solvıng Abılıtıes On Hıgher Order Thınkıng Skıll (Hots) Geometry Problems In Terms Of Spatıal Reasonıng - AM. Mega Purnamatati Mega; Meiliasasi; Karsih (Jurnal Elementaria Edukasia, 2024)
Geometric concepts in mathematics possess abstract properties that require a spatial reasoning process. Evaluating problem-solving abilities through HOTS (Higher-Order Thinking Skills) questions focusing on spatial reasoning is crucial for enhancing students' skills. The aims of this research are: (1) To understand the process of students' problem-solving skills in geometry HOTS based on spatial reasoning; (2) To analyze and pinpoint the challenges faced by students in solving geometry problems through HOTS questions that involve spatial reasoning. This study employs a qualitative approach with data analysis following the Miles and Huberman model, comprising data collection, data reduction, data presentation, and conclusion. The data gathered includes test outcomes, interviews, and documentation. The participants consist of 2 fifth-grade teachers and 3 students from SD N Lulut 05 and SD N Lulut 03. The findings indicate the necessity of regular training for students to effectively tackle HOTS questions and avoid difficulties. The test results showed that the spatial reasoning of the two schools reached 32% in the high category, while the HOTS geometry problem solving reached 30% in the high category. Students with strong spatial reasoning skills excel in solving HOTS problems, whereas those with moderate to low abilities encounter challenges in geometry problem-solving. Therefore, the spatial reasoning skills of students with different proficiency levels vary in addressing geometric problems compared to those with high mathematical abilities. A tailored learning strategy is essential to cater to the diverse needs of these students.